Characterizing the Seed Coat in the Subtribe Angraecinae (Orchidaceae, Vandeae) and Its Taxonomic Value - Roberto Gamarra; Emma Ortúñez; Pablo De La Fuente; Guillermo Valdelvira; Álvaro Hernando (Diversity)
The seeds of 121 species belonging to 38 genera of the subtribe Angraecinae (Orchidaceae) were studied in terms of their morphological characteristics under a scanning electron microscope (SEM). This study provided new data about the seed micromorphology of 17 genera and 100 species. Ten qualitative traits of the seed coat were analyzed, of which four were common for all the examined samples: elongated testa cells, anticlinal zone, curved transverse anticlinal walls, and sunken and narrow-to-not visible periclinal walls. These features are consistent with the epiphytic life-form of the genera studied. However, variation among genera was observed with reference to the seed shape, the morphology of the apical and the basal poles, the arrangement of the medial cells, the morphology of the longitudinal anticlinal walls, and the presence of testa extensions. A cluster analysis was performed, and two large groups were segregated according to the seed shape. Within a genus, all the examined species showed the same pattern of seed coat, except in Diaphananthe, Mystacidium, and Rhipidoglossum. On the other hand, the variation in the seed coat observed in Angraecum sensu lato supported its segregation into different genera. Our results perfectly fitted with recent taxonomic proposals.